CREATING THE VALUE CHAIN MILK BETWEEN BOSNIA AND HERZEGOVINA AND CROATIA - Plazibat, Ivana; Ćejvanović, Ferhat; Vasiljević, Zorica (Economics of Agriculture, 2016)
More than ever distribution of fast moving consumer goods (FMCG) between two neighbors, and ex partners in CEFTA 2006, Croatia and B&H becomes in focus of producers and retailers. Mainly because customs liberation that existed between two ex CEFTA partners ceased to be valid by entering Croatia in EU, and leaving CEFTA. Bosnia and Herzegovina was most important trading partner for Croatia, with the highest rate of trade liberalization within CEFTA 2006. At the same time Croatia was the most important trade partner for B&H. According to above mentioned the aim of this paper is to fnd out the possibility of the promotion of foreign trade between Bosnia and Herzegovina and Croatia for consumer products (milk and dairy products). Those FMCG earlier exchanged between two partners became today more costly. For that reason, to make these products more attractive to their consumers retailers and producers from both countries must jointly work to create greater value, i.e. compensate for the price difference trough creation of the value chain between B&H and Croatia retailers and producers.